2007
DOI: 10.2459/jcm.0b013e32801164cb
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcome of a prospective, controlled study of a disease management programme for elderly patients with heart failure

Abstract: A hybrid DMP for elderly heart failure patients improves outcomes and is cost-effective over a long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 26 publications
5
110
0
7
Order By: Relevance
“…Data from smaller (single-and two-centre) studies (128)(129)(130)(131)) demonstrated a significant reduction in hospitalization and a trend toward a reduction in mortality. A larger study (428 patients) by Cleland et al (132) examining home telemonitoring (HTM) compared with either nurse telephone support (NTS) or usual care found that there was no statistically significant difference between groups for the number of days lost as a result of death or hospitalization.…”
Section: Acute Decompensated Hf During Pregnancymentioning
confidence: 98%
See 1 more Smart Citation
“…Data from smaller (single-and two-centre) studies (128)(129)(130)(131)) demonstrated a significant reduction in hospitalization and a trend toward a reduction in mortality. A larger study (428 patients) by Cleland et al (132) examining home telemonitoring (HTM) compared with either nurse telephone support (NTS) or usual care found that there was no statistically significant difference between groups for the number of days lost as a result of death or hospitalization.…”
Section: Acute Decompensated Hf During Pregnancymentioning
confidence: 98%
“…Whether a DMP is a cost-effective way to manage these patients is not well established. The studies suggest a DMP may be cost effective or the extra cost associated with a DMP is acceptable (131,(139)(140)(141)(142). In a recent analysis by Whellan et al (143), an interesting concept based on the American system of reimbursement is presented.…”
Section: Acute Decompensated Hf During Pregnancymentioning
confidence: 99%
“…The Singapore population has, however, heterogeneous ethnic origins and their study enrolled 56% Chinese, 26% Malay and 17% Indian patients. 21 In terms of clinical outcomes, the effect of 24 which showed that disease management led to a lower admission rate (RR 0.253; 95% CI 0.065, 0.403; P = 0.014). In The Netherlands, the Deventer-Alkmaar heart failure study found an association between disease management and lower heart failure-related admissions and allcause deaths (RR 0.49; 95% CI 0.30, 0.81; P = 0.001).…”
Section: Y-h Chen Y-l Ho H-c Huang Et Al Chinese Home-based Intervmentioning
confidence: 99%
“…The meta-analysis showed a significant reduc- Reasons for exclusion: duplicates; editorials; letters; comments; reviews; protocols without data, without an intervention; not on transition, transition within hospitals, to nursing home, within specialist services; from emergency to the hospital; emergency conditions; education/health promotion; speci c intervention (eg, medication prescription only) 5 trials identied through the screening of reference lists 41 included in the systematic review * References 35,37,38,41,[44][45][46][47]50,54,55,57,60,67,68,73 T …”
Section: Effect On All-cause Hospital Readmissionmentioning
confidence: 99%